Aerobic training decreases bronchial hyperresponsiveness and systemic inflammation in patients with moderate or severe asthma: a randomised controlled trial. Issue 8 (10th June 2015) - França-Pinto, Andrezza; Mendes, Felipe A R; de Carvalho-Pinto, Regina Maria; Agondi, Rosana Câmara; Cukier, Alberto; Stelmach, Rafael; Saraiva-Romanholo, Beatriz M; Kalil, Jorge; Martins, Milton A; Giavina-Bianchi, Pedro; Carvalho, Celso R F
Abstract : Background: The benefits of aerobic training for the main features of asthma, such as bronchial hyperresponsiveness (BHR) and inflammation, are poorly understood. We investigated the effects of aerobic training on BHR (primary outcome), serum inflammatory cytokines (secondary outcome), clinical control and asthma quality of life (Asthma Quality of Life Questionnaire (AQLQ)) (tertiary outcomes). Methods: Fifty-eight patients were randomly assigned to either the control group (CG) or the aerobic training group (TG). Patients in the CG (educational programme+breathing exercises ( sham )) and the TG (same as the CG+aerobic training) were followed for 3 months. BHR, serum cytokine, clinical control, AQLQ, induced sputum and fractional exhaled nitric oxide (FeNO) were evaluated before and after the intervention. Results: After 12 weeks, 43 patients (21 CG/22 TG) completed the study and were analysed. The TG improved in BHR by 1 doubling dose (dd) (95% CI 0.3 to 1.7 dd), and they experienced reduced interleukin 6 (IL-6) and monocyte chemoattractant protein 1 (MCP-1) and improved AQLQ and asthma exacerbation (p<0.05). No effects were seen for IL-5, IL-8, IL-10, sputum cellularity, FeNO or Asthma Control Questionnaire 7 (ACQ-7; p>0.05). A within-group difference was found in the ACQ-6 for patients with non-well-controlled asthma and in sputum eosinophil and FeNO in patients in the TG who had worse airway inflammation. Conclusions: Aerobic training reduced BHR and serum proinflammatory cytokines and improved quality of life and asthma exacerbation in patients with moderate or severe asthma. These results suggest that adding exercise as an adjunct therapy to pharmacological treatment could improve the main features of asthma. Trial registration number: NCT02033122.